2014
DOI: 10.1016/j.ajo.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti–Vascular Endothelial Growth Factor Therapy on Choroidal Thickness in Diabetic Macular Edema

Abstract: Purpose To determine the effect of anti-vascular endothelial growth factor (VEGF) therapy on choroidal thickness in eyes with diabetic macular edema (DME) Design A retrospective, cohort analysis of 59 eyes from 59 patients with DME without prior anti-VEGF therapy Methods Choroidal thickness was measured using semi-automated segmentation of enhanced-depth imaging optical coherence tomography (EDI-OCT) images at 0.5mm intervals from 2.5mm nasal to 2.5mm temporal to the fovea. Changes in choroidal thickness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 28 publications
3
87
1
Order By: Relevance
“…5 ). When monitoring anti-VEGF therapy responses, the thickness of the ganglion cell layer (GCL), retinal nerve fiber layer (RNFL), and choroidal layer may decrease; a correlation with vision loss could only be shown for the GCL, whereas a decrease in choroidal thickness during therapy does not correlate with less vision gain [40][41][42] . On the other hand, a thick subfoveal choroid at baseline may predict good vision outcomes [43] .…”
Section: Evidencementioning
confidence: 99%
“…5 ). When monitoring anti-VEGF therapy responses, the thickness of the ganglion cell layer (GCL), retinal nerve fiber layer (RNFL), and choroidal layer may decrease; a correlation with vision loss could only be shown for the GCL, whereas a decrease in choroidal thickness during therapy does not correlate with less vision gain [40][41][42] . On the other hand, a thick subfoveal choroid at baseline may predict good vision outcomes [43] .…”
Section: Evidencementioning
confidence: 99%
“…Anti-VEGF treatment has demonstrated utility in improving visual and anatomical outcomes in DME (4)(5)(6)(7)(8)(9)(10) . The effects of anti-VEGF therapy on choroidal thickness in various diseases, including AMD and DM, have been reported in several previous studies (18,19) . Yiu et al demonstrated that central choroidal thickness decreases following anti-VEGF therapy for DME after 6 months (19) .…”
Section: Discussionmentioning
confidence: 73%
“…The effects of anti-VEGF therapy on choroidal thickness in various diseases, including AMD and DM, have been reported in several previous studies (18,19) . Yiu et al demonstrated that central choroidal thickness decreases following anti-VEGF therapy for DME after 6 months (19) . The present study also found a statistically significant decrease in choroidal thickness among patients following anti-VEGF injections.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…26 Therefore, blocking the action of VEGF on the choroid with anti-VEGF therapy, the permeability of the choroidal vasculature decreases, which can be noted by a decrease in CT. Lains et al 3 demonstrated a significant decrease in CT in DME patients following treatment with anti-VEGF therapy. In a more recent study by Yiu et al, 27 CT was also found to decrease significantly in patients receiving anti-VEGF therapy. In this study we included patients without prior anti-VEGF treatment to overcome this limitation.…”
Section: Discussionmentioning
confidence: 81%